Facile synthesis, antibacterial mechanisms and cytocompatibility of Ag–MnFe2O4 magnetic nanoparticles. Issue 12 (15th August 2020) - Ning, P.; Liu, C.C.; Wang, Y.J.; Li, X.Z.; Ranjithkumar, R.; Gan, Z.H.; Wu, Y.Y.; Fu, T.
Abstract: Magnetic MnFe2 O4 nanoparticles containing 0, 1 and 3 at.% silver, respectively were synthesized by one-pot sol-gel method for antibacterial applications in biomedical fields. Material characterizations indicate that MnFe2 O4 begins crystallization at 134 °C and oxidation at 450 °C, the grain size and agglomeration degree increase with the silver content and silver exists as metallic state for the particles. The saturation magnetization decreases with the sintering temperature and slightly increases with the silver content, with the maximum of 50.0 emu/g obtained. Antibacterial tests by plate counting and PI-Hoechst 33342 staining suggest that the antibacterial activity of Ag–MnFe2 O4 nanoparticles is silver content-dependent. Silver ions concentration measurement, β-galactosidase activity assay and transmission electron microscopic observation show that the antibacterial activity is dominated by the actions of the released silver ions, rather than the membrane cell impairment or reactive oxygen species-induced oxidative stress mechanism. MC3T3-E1 cell test demonstrates the best cytocompatibility of the nanoparticles with 3 at.% silver, which is likely related to the reduced cell endocytosis of the aggregated particles. The combination of magnetism, antibacterial activity and biocompatibility would make Ag–MnFe2 O4 nanoparticles a potential multi-functional material in various biomedical applications.